Investigating the mixing sequence and the Si content in SAPO-34 synthesis for selective conversion of methanol to light olefins using morpholine &/ TEAOH templates. Issue 21 (11th February 2016) - Ghavipour, Mohammad; Mehr, Amin Soleimani; Wang, Yao; Behbahani, Reza Mosayebi; Hajimirzaee, Saeed; Bahrami, Kiumars
Abstract : SAPO-34 as the commercialized catalyst of methanol to olefin (MTO) process was synthesized by single and mixed-template methods using TEAOH and morpholine. The mixing sequence in gel preparation and the optimum Si content were investigated. Abstract : SAPO-34 which is known as the commercialized catalyst of methanol to olefin (MTO) process was synthesized by single and mixed-template methods using TEAOH and morpholine. For the first time, different mixing sequences of initial materials for gel preparation were examined according to four different procedures. The optimum synthesis procedures were determined by characterizing the prepared catalysts by XRD, XRF, SEM, BET, TPD and TGA techniques. It was found that the sequence of mixing was of crucial importance in SAPO-34 synthesis and the optimum mixing sequence was strongly related to the type of template. The Si content in the gel composition was also varied (SiO2 /Al2 O3 = 0.1 to 0.6 or % Si/Si + Al + P = 2.4 to 13) and, interestingly, not just the strength and amount of acid sites but also the particle size and surface area of the resulting catalysts were dramatically changed from 0.6 μm and 691 m 2 gcat −1 to 1.6 μm and 468 m 2 gcat −1, respectively. The catalysts performances, life times and products distributions were also analyzed in MTO reaction by a fixed bed reactor at 400–430 °C. The SAPO-34 sample using TEAOH with SiO2 /Al2 O3 of 0.3 showed the best activity among single-template samples (light olefin selectivity of 78.9%). Mixed-template SAPO-34 samples were also prepared by two synthesis procedures and one of them showed a higher surface area (543 m 2 g −1 ) and smaller particles (1.1 μm) than the single-template SAPO-34 with the same Si content. The longest catalyst life time with light olefin selectivity of 81.9% was recorded on this mixed-template SAPO-34 at 400 °C and WHSV = 1 gMeOH gcat −1 h −1 .